Critical Realism in Information Systems Research - Mingers, John; Mutch, Alistair; Willcocks, Leslie (MIS Quarterly, 2013)
Critical realism offers exciting prospects in shifting attention toward the real problems that one faces and their underlying causes. As such, it offers a robust framework for the use of a variety of methods in order to gain a better understanding of the meaning and significance of information systems in the contemporary world. One of the interesting tensions is that Archer's argument for the centrality of reflexivity in contemporary conditions tends to downplay both routine action and tacit forms of knowing, whereas a considerable volume of work on organizations and IS stresses the centrality of both. A great strength of the paper is that MA is used in an in-depth study to reveal over a long time line the processes and mechanisms that explain how the ICT for development trajectory emerged from the interplay of interactions at different levels of players in global, national, public, private, third sector, and civil society institutions and organizations.